2014
DOI: 10.1002/pca.2546
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Differentiation and Quality Evaluation of Commercial Asian and American Ginsengs based on a UHPLC–QTOF/MS/MS Metabolomics Approach

Abstract: The method provided important fingerprint information for authentication and evaluation of Asian and American ginsengs from various commercial products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Similarly, consumers primarily evaluate the quality of ginseng on the basis of morphological features. In our previous study, we investigated the characteristic chemical markers for differentiating commercial Asian and American ginsengs [15]. The results indicated that the chemical profiles varied between Asian and American ginsengs, forest-grown and field-grown sun-dried Asian ginsengs, as well as wild and cultivated American ginsengs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, consumers primarily evaluate the quality of ginseng on the basis of morphological features. In our previous study, we investigated the characteristic chemical markers for differentiating commercial Asian and American ginsengs [15]. The results indicated that the chemical profiles varied between Asian and American ginsengs, forest-grown and field-grown sun-dried Asian ginsengs, as well as wild and cultivated American ginsengs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent metabolomics study, most of which have focused on chemical markers and quality control between Asian ginseng and American ginseng21222324. This work provides new insight into different metabolome disturbance in urine along with a four-week administration of Asian ginseng and American ginseng coupling the GC-MS platform which presents unique strengths of high sensitivity, reproducibility and available spectral libraries25.…”
mentioning
confidence: 99%
“…Cui, Wu, Wang, and Wang () have used GC‐MS and the electronic nose to investigate Asian and American ginseng, which were scattered significantly in both plots (Cui et al, ). It had reported that Asian ginsengs were divided into two groups by OPLS‐DA and PCA, and these classifications meet their specifications as “forest ginseng” or “sun‐dried ginseng.” It indicated that some differences exist in the chemical profiles of the two groups (Chen et al, ). PCA analysis showed that the quality of AR‐5M, AR‐5R and AR‐4R was mostly similar to that of native ginseng.…”
Section: Discussionmentioning
confidence: 99%